Prevalence of Bacteriuria in Pregnant Women Visiting Provincial Hospital, Janakpurdham, Nepal - Yadav, Nagendra Prasad; Thakur, Rudra Narayan; Yadav, Rakesh Kumar (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Considering the importance of urinary tract infection (UTI) in pregnant women which is responsible for several complications, its diagnosis and treatment are essential to maintain the health of mother and baby.The purpose of the present study was to evaluate the isolation and identification of Escherichia coli from the UTI suspected pregnant women visiting at provincial Hospital Janakpur. MATERIALS AND METHODS: A total of 200 mid-stream urine samples were collected from UTI suspected pregnant women of 18 to 45 years visiting antenetal OPD in Provincial Hospital Janakpur in between February 2021 to April 2021. The collected urine samples were processed in the microbiology department of the Model Multiple College, Janakpur. Standard Microbiological procedures were followed. RESULTS: The Escherichia coli were predominant identified as 17 (35.41%). Patients aged between 25-30 years were mostly infected 35 (72.9%). The majority of bacteria isolated were more sensitive to Cephalexin and nitrofurantoin. CONCLUSIONS: Escherichia coli is one of the most important pathogen for UTI in pregnant women. The majority of bacteria isolated in the present study were more sensitive to Cephalexin and nitrofurantoin.